Improving creep resistance and durability forecasting of Balau wood–PGFRP composite cross-arms using sleeve retrofitting for transmission towers - Sukumaar, Vijayvignesh Namasivayam; Ishak, Mohamad Ridzwan; Yidris, Noorfaizal; Mazlan, Norkhairunnisa; Muhammad Rizal, Muhammad Asyraf (Elsevier B.V., 2025)
Cross-arms of high-voltage transmission towers are traditionally made from wood or pultruded glass fibre reinforced polymer (PGFRP) composites, but both materials face limitations in creep resistance and long-term durability. This study proposes a novel plug-in type SS304 stainless steel sleeve retrofit designed to enhance the mechanical performance and service life of Balau wood–PGFRP composite cross-arms under real-world operational loads. A comprehensive experimental program was conducted using four distinct loading configurations, three-point bending (3 PB), uniformly distributed load (UDL), uniformly varying load (UVL), and concentrated point load (CPL), across single main member cross-arm specimens. Mechanical deflection and long-term flexural creep tests were performed in accordance with ASTM D790 and D2990 standards. Results showed that the sleeve reinforcement improved instantaneous deflection and creep resistance by up to 62 % and 72 %, respectively. Among the loading types, CPL exhibited negligible influence on real-world failure modes, while UDL and UVL collectively replicated the effects observed under 3 PB, validating the 3 PB condition as the most representative for durability forecasting. Long-term prediction using Findley's power-law model revealed that the sleeve-reinforced cross-arm retained up to 85 % more stiffness after 50 years compared to the virgin composite and Balau wood counterparts. The proposed retrofitting method demonstrates significant potential for extending the service life of transmission tower cross-arms while enabling cost-effective maintenance and structural resilience.